Association between sleep and meteorology in late-onset depression patients - Yu Guo; Yan Sun; Zi-fan Zhu; Hao Geng; Si-wen Lv; Lou-feng Zhang; Peng-yu Xie; Xin-yu Gao; Yin-song Lu; Xiao-ming Kong (BMC Psychiatry)
Abstract Objective To explore the sleep characteristics in different seasons and whether meteorology are related to sleep quality in LOD patients. Methods A total of 241 LDO patients from Anhui Mental Health Center (2019–2023) were recruited. Meteorological data from the U.S. National Centers for Environmental Information ( https://www.ncei.noaa.gov/maps/daily/ ). Difference analysis, correlation analysis, multiple linear regression models and restricted cubic splines to evaluate the relationship between season, meteorology and sleep quality among LOD patients. Results Compared with winter and spring, LOD patients have higher sleep efficiency and shorter awakening time in summer and autumn (p < 0.05). Higher precipitation was associated with improved sleep efficiency (β = 0.193, 95% CI [0.044, 0.685], p = 0.026), and associated with decreased awakening time (β =—0.194, 95% CI [-3.712, -0.252], p = 0.025). Higher sunshine intensity was related to increased rapid eye movement (REM) sleep duration (β = 0.27, 95% CI [0.024, 0.151], p = 0.007) and REM% (β = 0.26, 95% CI [0.005, 0.036], p = 0.010). Sunshine intensity exhibited an inverted U-shaped relationship with awakening time (inflection points at 160.8 Wh/m2, p = 0.031, p-nonlinear = 0.008) and exhibited U-shaped relationship with sleep efficiency (inflection points at 166.9 Wh/m2, p = 0.081, p-nonlinear = 0.029). Temperature exhibited U-shaped relationship with sleep efficiency (inflection points at 20.3 °C, p = 0.044, p-nonlinear = 0.030), total sleep time (inflection points at 20.7 °C, p = 0.006, p-nonlinear = 0.008) and stage 2 of non-rapid eye movement (N2) duration (inflection points at 18.5 °C, p < 0.001, p-nonlinear < 0.001). Specific humidity exhibited U-shaped relationship with sleep efficiency (inflection points at 11.9 g/kg, p = 0.123, p-nonlinear = 0.042) and N2 duration (inflection points at 11.7 g/kg, p = 0.028, p-nonlinear = 0.008), and exhibited inverted U-shaped relationship with stage 1 of non-rapid eye movement (N1) duration (inflection points at 10 g/kg, p = 0.007, p-nonlinear = 0.020). Conclusion This study demonstrates that sleep quality is poorest in LOD patients under moderate sunshine intensity, temperature, and humidity conditions, whereas extreme conditions enhance sleep efficiency and N2 duration while reducing awakening time.